Optimizing the Legality of MSME Products through Halal Certification Assistance in Jabon, Sidoarjo - Poppy Diana Sari; Lukman Hudi; Syarifa Ramadhani Nurbaya; Atik Wahyuni; Muhammad Ainur Rafdiansyah; Lailis Sabilah (SINAR SANG SURYA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the local economy, yet they still face challenges in product legality, particularly regarding halal certification. This community service initiative aims to optimize the legality of MSME products by providing halal certification assistance to bread and cake producers in Kedung Pandan Village, Jabon - Sidoarjo. This program is implemented by a community service team from the Food Technology Study Program at Muhammadiyah University of Sidoarjo, utilizing an educational approach, outreach, and direct assistance in the halal certification application process. The implementation method includes participant identification, education and outreach regarding halal certification regulations and procedures, and technical assistance in processing documents and submitting applications through the applicable system. The results of the activity demonstrated an increased understanding among participants regarding the importance of halal certification and product legality procedures. This was evident in the improved knowledge assessment results after the mentoring activity. This activity also raised awareness among MSMEs to improve the quality and safety of their products. As a form of program sustainability, partners expect continued assistance in obtaining Home Industry Product (P-IRT) permits and other training to improve the business capacity, competitiveness, and sustainability of MSMEs in the region. Thus, the program is expected to go beyond halal certification and contribute to strengthening the legality and overall development of MSMEs.